Community-Driven Media Literacy And Resilience Building - Ida, Rachmah; Kinasih, Sri Endah; Febriyanti, Syafrida Nurrahmi; Puspa, Ratih; Romadhona, Mochamad Kevin (Journal of Community Service, 2024)
During the Covid-19 pandemic in Indonesia, social media and mainstream mass media have been flooded with viral content, challenging the dichotomy of acceptance and resistance to prevention programs. To create resilience, education-preventive efforts are needed to empower vulnerable communities. A community service program aims to educate the public about digital media dynamics and teach people to create content about preventing transmission and creating resilience. The program focuses on raising community awareness, particularly among young children, and demonstrates that people's perceptions and constructions towards COVID-19 prevention programs vary